Pelatihan Kader Posyandu Kota Cimahi Dan Pembentukan Dokter Gigi Kecil Untuk Pencegahan dan Deteksi Dini Karies Gigi Di Wilayah Puskesmas Kecamatan Cimahi Tengah Kota Cimahi: Training of Posyandu Cadres in Cimahi City and the Formation of Little Dentists for the Prevention and Early Detection of Dental Caries in the Health Center Area of Cimahi Tengah District, Cimahi City - Praptiwi, Yenni Hendriani; Utami, Ulfah; Widyastuti, Tri; Nariswari PD1, Avisa; Salsabilla, Trina Deswita; Kusumawardani, Angelica Sasha; Pasaribu, Cindy Aryanti; Handayani, Ratna Dwi (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2025)
Dental caries is one of the serious health problems of school-age children. Efforts to maintain oral health from an early age need to be done in preventing dental caries. Dental health maintenance behavior is by knowing the causes of caries and how to brush teeth properly. The purpose of this service is to prevent dental caries that occurs in elementary school children and early detection in children in posyandu through training of small dentists and posyandu cadres. This type of research is quantitative research. The research instruments are lectures, discussions, and demonstrations. The results of the implementation of education, there are two materials presented, namely about early detection of dental caries and the correct steps in brushing teeth. The counseling was attended by teacher representatives, children from Cimahi Mandiri Elementary School 1 to 5, and posyandu cadres. Children and posyandu cadres were taught about the problems that arise when not maintaining oral health and given a demonstration of how to brush their teeth properly. The conclusion of this service is that after receiving education on early detection of dental caries and how to brush teeth properly and correctly, it is hoped that these representatives of small dentists and posyandu cadres can demonstrate how to brush teeth properly and correctly and convey information about caries detection to the target. Keywords: training; dental caries; tooth brushing; little dentist; cadres; dental health.